Decision-making process in the World Trade Organization (WTO) : an appraisal of the concensus principle in general decision-making - Belhacel, Fateh (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
The legitimacy and the credibility of any international organizations depend primarily on the effectiveness of its decision-making process, in particular the extent to which such a process could produce dependable and acceptable decisions. The inability of World Trade Organization (WTO) to address its overwhelming problems is essentially the failure of the consensus principle in the general decision-making which drastically failed to harmonise distinct and varied contending interests. This study compares the application of the consensus-based decision-making under both the GATT and WTO system. It elaborates on the reasons that have led to more successes in the decision-making mechanism of the former (GATT) compared to that of the latter (WTO). The principle of consensus has various advantages, most especially in terms of protecting the sovereign equality of the WTO members by granting each and every one the right of veto. However, with the enlargement of the WTO membership and scope, and considering the binding nature of the WTO rules, the consensus practice has become extremely cumbersome, and increasingly caused delays and stagnated the WTO negotiations. In view of these developments, this study has revealed an imminent need for reforms in the WTO decision-making process, within the parameters of the consensus principle. Though available literature calls for reforms in the process of consensus-based decision-making, but these proposals are unclear, obscure and complex. The proposition within the purview of this study is that the WTO primarily needs to differentiate between procedural matters (“housekeeping”) and substantive matters. It submits that the majority vote system should be used for the former whereas the latter would continue to be decided according to the consensus principle. However, such a principle must be flexible in a way that if a critical mass of members is in favor of the proposed decision, other members will abstain from blocking the consensus (the Critical Mass approach). Finally, it proposes the establishment of an Elected Executive Board to ease the process of building consensus rather than the informal Green Room meetings.